UPAYA MENINGKATKAN HASIL BELAJAR PERMAINAN TONNIS MENGGUNAKAN MODIFIKASI MEDIA PEMBELAJARAN - Ahsan Hakim Fariza; Rony Syaifullah (PJKR FKOR UNS, 2018)
ABSTRACTThe purpose of this research is to improve the learning outcomes of the tonnis game in fourth grade students in SD Negeri Banyuanyar II Surakarta in academic year 2017/2018.This research is a Classroom Action Research (PTK). This research was conducted in two cycles, each cycle consisting of four stages: planning, implementation, observation and reflection. Subjects in Classroom Action Research are fourth grade students of SD Negeri Banyuanyar II Surakarta, amounting to 36 students consisting of 21 male students and 15 female students. Sources of data in this study were obtained from students, researchers and teachers as collaborators. Data collection techniques use tests and observations. Data validity using data triangulation technique. Data analysis using qualitative descriptive technique based on qualitative analysis percentage.The results of the research on prasiklus stage are only 12 students who completed with the percentage 33.33% and 24 students not complete with the percentage of 66.67%. First cycle obtained the results of student learning that has been completed as many as 25 students (69.44%) and 11 students are not complete (30.56%). The acquisition of affective averages (72.22%), psychomotor (58.33%) and cognitive (77.78%). Second cycle obtained the results of student learning that has been completed as many as 28 students (77.78%) and 8 students is not complete (22.22%). The acquisition of affective averages (100%), psychomotor (86.11%) and cognitive (77.78%). Based on the analysis results from cycle I and cycle II showed a significant increase and according to achievement targets. Based on the research results obtained the conclusion that: Modification of learning media can improve the learning outcomes of basic motion of the game tonnis on the fourth grade students of SD Negeri Banyuanyar II Surakarta academic year 2017/2018.